AN ANALYSIS OF THE INTENTION TO PURCHASE ON THE COLLECTIVE BUYING WEBSITES THROUGH PSYCHOLOGICAL, SOCIOCULTURAL AND SITUATIONAL FACTORS - Souza, Erivaldo Lopes de; Silva, Luiz Bueno da; Lima Neto, Eufrásio de Andrade; Lima, Márcio Botelho da Fonseca; Paiva, Jonas Alves (Cadernos do IME - Série Estatística, 2017)
DOI: 10.12957/cadest.2017.25443 This article proposes to use empirical models, with good adjustment, that can provide an informative measure on the intention to buy consumers considering information about socio-cultural, psychological and situational factors associated with them. It is expected that a measure of probability provided by a model such as that proposed can be useful in strategic marketing decisions where consumers' intention to buy.To achieve the objective, initially interviewed 384 Internet users in places with large circulation of people the city of João Pessoa, Paraíba, Brazil. Then the data obtained from interviews, were used to estimate those models. These models were based on assumptions of theories of the cognitive approach of consumer behavior, especially the Theory of Reasoned Action. The instrument used for data collection was a questionnaire containing market research questions related to psychological factors, sociocultural and situational consumer. The analysis considered only regression models of the class of generalized additive models.The most successful model presented nine variables and a single non-parametric term, obtained from smoothing splines. This model had a pseudo-R2of 0,89 and allowed to reach a percentage of correct trials of the observations of the sample equal to 94%. Keywords: Purchases intention, Regression model, Generalized Aditive Models, Consumer Behavior.